2011
DOI: 10.2119/molmed.2010.000134
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Leptin Receptor Long Isoform (LepRb)-STAT3 Signaling Pathway in Brain Fat Mass- and Obesity-Associated (FTO) Downregulation during Energy Restriction

Abstract: Glycine N-methyltransferase (GNMT) is a major hepatic enzyme that converts S-adenosylmethionine to S-adenosylhomocysteine while generating sarcosine from glycine, hence it can regulate mediating methyl group availability in mammalian cells. GNMT is also a major hepatic folate binding protein that binds to, and, subsequently, may be inhibited by 5-methyltetrafolate. GNMT is commonly diminished in human hepatoma; yet its role in cellular folate metabolism, in tumorigenesis and antifolate therapies, is not unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 68 publications
1
34
2
4
Order By: Relevance
“…The exact mechanism for how this gene affects BMI and obesity remains unclear, but it was hypothesized that the FTO gene is involved in food intake, as it is highly expressed in the hypothalamus [35] and was also found to be involved in leptin signaling at the hypothalamus [36]. Animal studies showed that this gene controls energy expenditure and its absence in mice resulted in a leaner body mass and reduced adipocytes [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for how this gene affects BMI and obesity remains unclear, but it was hypothesized that the FTO gene is involved in food intake, as it is highly expressed in the hypothalamus [35] and was also found to be involved in leptin signaling at the hypothalamus [36]. Animal studies showed that this gene controls energy expenditure and its absence in mice resulted in a leaner body mass and reduced adipocytes [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Our works on identification of visfatin (also known as NAMPT) as a target for stroke therapy provide new insights into understanding of adipose-brain axis [5][6][7][8][9]. In addition, we demonstrate a novel leptin receptor signaling in the brain for control of body weight under caloric restriction, suggesting FTO may be a therapeutic target for leptin resistance obesity [10]. We also studied the adipokines in adipose renin-angiotensin system [3] and the inflammatory adipokines such as TNFa [11].…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, homozygous AA individuals are more prone to an elevated post‐prandial appetite level, which is linked to an interaction between the FTO genotype and circulating levels of ghrelin, a key mediator of digestive behavior (Karra et al, ). Other studies also suggest an effect of FTO on the regulation of proteins in pathways involved in energy intake, such as leptin levels (Labayen et al, ) and leptin sensitivity (Wang et al, ), and other signaling proteins (Lin et al, ; Rask‐Andersen et al, ). The FTO ‐rs9939609 genotype is also associated with some metabolites, with evidence having been obtained of changes in phospholipid and amino acid metabolisms that may be linked to obesity and type 2 diabetes in A allele carriers (Kim et al, ).…”
Section: Discussionmentioning
confidence: 98%